2011
DOI: 10.1523/jneurosci.1395-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and 17β-Estradiol Differentially Modulate the M-Current in Neuropeptide Y Neurons

Abstract: Multiple K+ conductances are targets for many peripheral and central signals involved in the control of energy homeostasis. Potential K+ channel targets are the KCNQ subunits that form the channels underlying the M-current, a sub-threshold, non-inactivating K+ current that is a common target for G-protein coupled receptors. Whole-cell recordings were made from GFP (Renilla)-tagged NPY neurons from the arcuate nucleus of the hypothalamus using protocols to isolate and characterize the M-current in these orexige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
135
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(142 citation statements)
references
References 57 publications
(109 reference statements)
6
135
0
1
Order By: Relevance
“…Most interestingly, ghrelin is able to modulate native Kv7/KCNQ channels expressed in nigral dopaminergic neurons, small DRG neurons and CA1 pyramidal neurons. In addition to the indicated three different types of neurons, ghrelin receptor and Kv7/KCNQ channels are also individually expressed in pituitary, neuropeptide Y neurons in hypothalamus and cortex 21,[40][41][42] , all of these suggest that the ghrelin signalling and Kv7/KCNQ suppression are likely common pathways primarily utilized by the central nervous system. Neuronal excitability is closely linked to dopamine release in the brain 43 and increased firing of dopamine neurons accelerates the dopamine release in the striatum, nucleus accumbens and cerebral cortex 43,44 .…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinmentioning
confidence: 96%
See 1 more Smart Citation
“…Most interestingly, ghrelin is able to modulate native Kv7/KCNQ channels expressed in nigral dopaminergic neurons, small DRG neurons and CA1 pyramidal neurons. In addition to the indicated three different types of neurons, ghrelin receptor and Kv7/KCNQ channels are also individually expressed in pituitary, neuropeptide Y neurons in hypothalamus and cortex 21,[40][41][42] , all of these suggest that the ghrelin signalling and Kv7/KCNQ suppression are likely common pathways primarily utilized by the central nervous system. Neuronal excitability is closely linked to dopamine release in the brain 43 and increased firing of dopamine neurons accelerates the dopamine release in the striatum, nucleus accumbens and cerebral cortex 43,44 .…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinmentioning
confidence: 96%
“…Both Kv7/KCNQ channels and GHS-R are expressed in the SNc, hippocampus, dorsal root ganglion (DRG), hypothalamus and cortex 11,15,[17][18][19][20][21][22][23] . KCNQ channels are also negatively modulated by G-protein-coupled receptors via Gq and/ or G 11 activated phospholipase C (PLC)-mediated signal pathway [24][25][26] .…”
mentioning
confidence: 99%
“…The NPY, GABA B-R1, and GABAB-R2 primer sequences were as previously published (36,58). Mouse PI3K p110␤ primers (218 bp product; acc.…”
Section: E633 Rapid Estrogen Signaling In Npy/agrp Neuronsmentioning
confidence: 99%
“…These data collectively suggest that E 2 suppresses or augments GABA B -mediated currents in these orexigenic neurons through binding ER␣ or a putative Gq-mER, respectively. We previously have shown that NPY/AgRP neurons express ER␣ transcript and protein (36), and the cloning of the Gq-mER is a work in progress. Since the NPY/AgRP neurons that differentially responded to E 2 showed no physiological (i.e., resting membrane potential or input resistance) or anatomic (Fig.…”
Section: E637 Rapid Estrogen Signaling In Npy/agrp Neuronsmentioning
confidence: 99%
See 1 more Smart Citation